Cropping system intensification: vegetable pea can replace fallow between rainfed monsoon rice and irrigated spring rice - Malik, A.I.; Nasim, M.; Flower, K.; Hossain, M.A.; Rahman, M.S.; Anwar, B.; Ali, M.O.; Rahman, M.M.; Erskine, W. (Cambridge University Press, 2017)
The Eastern Gangetic Plain is among the world's most intensively farmed regions, where rainfed and irrigated agriculture coexist. While the region and especially Bangladesh is a major producer of rice (Oryza sativaL. ssp.indica), there is potential to further develop sustainable rice production systems. Specifically, there is scope to include a replacement crop for the short fallow between rice crops in the dominant cropping pattern of rainfed monsoon rice harvest followed by irrigated spring rice. The aim of the current research was to identify a suitable cool-season legume crop – pea (Pisum sativumL.) or lentil (Lens culinarisMedik. ssp.culinaris) – that could be grown in the brief period between rice crops. The study comprised four crop sequence experiments comparing legume cultivars differing in maturity grown in between both long and short duration rice cultivars. These experiments were done at the Bangladesh Rice Research Institute regional station at Rajshahi over three cropping cycles. This was followed by an evaluation of pea vs. fallow between rice crops on three farmers’ fields in one cropping cycle. Here it is demonstrated that green pod vegetable pea is one of the best options to intensify the rainfed monsoon rice–fallow–spring irrigated rice cropping system, notwithstanding other remunerative rabi cropping options that could displace boro rice. The inclusion of an extra crop, pea as green pod vegetable, increased farm productivity by 1·4-fold over the dominant cropping sequence (rice–fallow–rice) and farm net income by fourfold. The study highlighted the advantages in total system productivity and monetary return of crop intensification with the inclusion of a pea crop between successive rice crops instead of a fallow period.